إبداع المعلم في تعليم كتاب التراث لترقية مهارة القراءة للطالبات في المعهد الإسلام الفرقان تجوكير جومبانج - Vina Alafi Hidayah; Isniyatun Niswah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This study examines the teaching of classical Arabic books (kutub al-turath) at Al-Furqan Islamic Institute, Jombang. Classical texts are a key component of Arabic education, essential for developing students’ ability to read formal Arabic (Fusha). However, many students find these texts difficult and boring due to monotonous teaching methods, resulting in decreased interest and comprehension. The research investigates: 1) how classical texts are taught at the institute, 2) teachers’ creative strategies in delivering these materials, and 3) how these innovations improve students’ reading skills. Using a qualitative descriptive approach, data was collected through observation, interviews, and documentation, then analyzed through data reduction, display, and conclusion drawing. Results show that classical texts are taught twice a week using structured methods such as discussions and mind maps to enhance understanding. Teachers creatively incorporate interactive games, competitions, and oral tests to make learning engaging and relevant. These innovations improve students’ motivation, comprehension, and connection to the texts as life guides, not just linguistic content. Reading classical texts also supports students' spiritual growth, and creative strategies like role-play, virtual scavenger hunts, and group discussions effectively improve their reading abilities and engagement.